2016
DOI: 10.1177/0885328215626361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and bioactive properties of nano bioactive glass and segmented polyurethane composites

Abstract: Composites of glutamine-based segmented polyurethanes with 5 to 25 wt.% bioactive glass nanoparticles were prepared, characterized, and their mineralization potential was evaluated in simulated body fluid. Biocompatibility with dental pulp stem cells was assessed by MTS to an extended range of compositions (1 to 25 wt.% of bioactive glass nanoparticles). Physicochemical characterization showed that composites retained many of the matrix properties, i.e. those corresponding to semicrystalline elastomeric polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In general, the mechanical properties of composites of PU/Ti were lower than PU/bioactive glass composites in spite of their higher rigidity, except for the Young's modulus that was significantly higher at low strain rates. 4 However, the mechanical properties of these composites are far from those exhibited by trabecular bone from human femur (17.5 AE 1.12 GPa) or cortical bone (22.1 GPa) measured by ultrasonic technique. 29…”
Section: Thermal Propertiesmentioning
confidence: 93%
See 3 more Smart Citations
“…In general, the mechanical properties of composites of PU/Ti were lower than PU/bioactive glass composites in spite of their higher rigidity, except for the Young's modulus that was significantly higher at low strain rates. 4 However, the mechanical properties of these composites are far from those exhibited by trabecular bone from human femur (17.5 AE 1.12 GPa) or cortical bone (22.1 GPa) measured by ultrasonic technique. 29…”
Section: Thermal Propertiesmentioning
confidence: 93%
“…23,24 At 1636 cm À1 , urea absorptions were detected in agreement with previous works. 4,10,25 In composites, infrared absorptions from the PU remain and bands from Ti were not observed since metal-metal bonds cannot be detected by conventional FTIR spectrometers using ATR technique or because they were masked due to their low concentration. For pristine titanium only adsorbed water (3432 cm À1 ), carbon-containing species (2921 and 2852 cm À1 ), and oxidized titanium (705 cm À1 ) were observed.…”
Section: Ti Distribution In Pu/ti Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other paper by the same research group, PU glutamine-based segmented polyurethanes with 5–25 wt.% bioactive glass nanoparticles were prepared and it has been found that compositions with low content of bioactive glass nanoparticles are promising material for applications such as guided bone regeneration membranes [ 111 ].…”
Section: Pu-based Materials In Bone Tissue Engineeringmentioning
confidence: 99%